Proceedings of 5th International Conference in Software Engineering for Defence Applications SEDA 2016 - Ciancarini, Paolo; Litvinov, Stanislav; Messina, Angelo; Sillitti, Alberto; Succi, Giancarlo (Advances in Intelligent Systems and Computing, 2018)
This book presents high-quality original contributions on new software engineering models, approaches, methods, and tools and their evaluation in the context of defence and security applications. In addition, important business and economic aspects are discussed, with a particular focus on cost/benefit analysis, new business models, organizational evolution, and business intelligence systems. The contents are based on presentations delivered at SEDA 2016, the 5th International Conference in Software Engineering for Defence Applications, which was held in Rome, Italy, in May 2016. This conference series represents a targeted response to the growing need for research that reports and debates the practical implications of software engineering within the defence environment and also for software performance evaluation in real settings through controlled experiments as well as case and field studies. The book will appeal to all with an interest in modeling, managing, and implementing defence-related software development products and processes in a structured and supportable way.